Proniosomal Gel for Topical Delivery of Rutin: Preparation, Physicochemical Characterization and In Vitro Toxicological Profile Using 3D Reconstructed Human Epidermis Tissue and 2D Cells - Iulia Pinzaru; Alina Tanase; Virgil Enatescu; Dorina Coricovac; Flavia Bociort; Iasmina Marcovici; Claudia Watz; Lavinia Vlaia; Codruta Soica; Cristina Dehelean (MDPI AG, 2021)
Rutin (Rut) is a natural flavonol, well-known for its broad-spectrum of therapeutic effects, including antioxidant and antitumoral activities; still, it has a reduced clinical outcome due to its limited solubility in aqueous solutions. To overcome this drawback, this study proposes a novel formulation for rutin as a proniosomal gel for cutaneous applications. The gel was prepared by coacervation phase-separation method and complies with the standard requirements in terms of particle size (140.5 ± 2.56 nm), zeta potential (−27.33 ± 0.09 mV), encapsulation capacity (> 50%), pH (7.002 ± 0.18) and rheological properties. The results showed high biocompatibility of the gel on the 3D reconstructed human epidermis model characterized by increased viability of the cells and a lack of irritant and phototoxic potential. The evaluations on 2D cells confirm the preferential cytotoxic effect of Rut on melanoma cells (IC50 value = 8.601 µM, nuclear fragmentation) compared to normal keratinocytes. Our data suggest that the proniosomal gel is a promising drug carrier for Rut in the management and prevention of skin disorders.